Experimental assessment of biomass feedstock gasification in a high-temperature continuous solar gasifier - Srirat Chuayboon; Stphane Abanades; Sylvain Rodat; Houssame Boujjat (My University, 2019)
Solar steam gasification of biomass was performed in a 1.5 kWth continuous particle-fed solar reactor at high temperature (1100-1300 °C) using real high-flux solar radiation provided by a parabolic dish solar concentrator. A comprehensive parametric study considering different lignocellulosic biomass feedstocks, biomass feeding rates, and operating temperatures was conducted for optimizing the syngas production and assessing the gasification performance. Different biomass feedstocks were continuously fed and gasified with H2O to produce syngas, thus demonstrating the suitability of the reactor operated compatibly with different biomass variants. A significant beneficial enhancement of the syngas yield when increasing temperature was highlighted. Increasing biomass feeding rate considerably promoted the syngas yields, and the syngas production (especially H2) was more affected by the biomass feedstock (chemical composition) than by the particle size in the considered range (0.3-4 mm). Moreover, an increase in the biomass feeding rate inherently reduced the solar processing duration (for a given biomass amount processed), thus in turn promoting efficient solar energy storage into syngas with the energy upgrade factor (U) up to 1.24 and solar-to-fuel energy conversion efficiency (ηsolar–to–fuel) up to 29%.
Keywords: Wood gas generator; Biomass gasification; Chemical Looping and Thermochemical Processes